The Correlation of Different Cotinine Levels With Questionnaire Results: A Comparative Study for Different Measurement Methods of the Adolescent Smoking Rate in Korea. (July 2015) - Park, Myung Bae; Nam, Eun Woo; Lee, Seon Kui; Kim, Chun-Bae; Ranabhat, Chhabi
This study compares the results of the Korea National Health and Nutrition Examination Survey (Self-Reported; KNHANEs [SR]) survey with urine-cotinine concentration (UCC) and the official index issued by the Korea Youth Risk Behavior Web-based Survey (KYRBS). We established standard cutoffs of 20 ng/mL, 30 ng/mL, 50 ng/mL, and 100 ng/mL to compare the results of UCC testing with those of self-reporting methods. The KYRBS demonstrated an overall current smoking rate of 12.25%, while the KNHANEs measured an overall rate of 9.63%. The UCC20 reported the highest current smoking rate at 25.6% overall. Methods that detected a lower prevalence of current smoking, in declining order, were the UCC30, UCC50, UCC100, online survey, and the KNHANEs (SR). The results of this study show that online surveys on smoking administered to adolescents have fewer false responses compared with the KNHANEs (SR). However, compared with UCC testing, online surveys still significantly underreport adolescent smoking rates.